Vacancy clustering in pure metals: Some first principle calculations of positron lifetimes and momentum distributions - Luna, Carla Romina (2013)
First results of a systematic study on the vacancy clustering process in Al, Cu, Mg and Nb are presented. To this aim first principle calculation of positron lifetimes and positron-electron momentum distributions were performed. We test the reliability of the computational scheme used by comparing some of the calculated results with experimental ones.